Pedigree analysis and epidemiological features of idiopathic congenital talipes equinovarus in the United Kingdom: a case-control study - Maffulli N; Sharp L; Chesney D; Barker S; Cardy AH; Miedzybrodzka Z (BMC Musculoskeletal Disorders, 2007)
Abstract Background Congenital talipes equinovarus (CTEV) is a common developmental disorder of the foot, affecting between 1 and 4.5 per 1000 live births. The aetiology is not well elucidated. While both genetic and environmental factors are implicated, no specific genes have been identified and little is known about environmental risk factors. Methods We conducted a case-control study of idiopathic congenital talipes equinovarus (ICTEV) in the United Kingdom. 194 cases and 60 controls were recruited. Pedigrees were obtained for 167 cases. Results The rank of the index pregnancy, maternal education and caesarean delivery were significantly associated with ICTEV risk in a multivariate model. There were suggestions that maternal use of folic acid supplements in the three months before the pregnancy decreased ICTEV risk, and that parental smoking during the pregnancy increased risk, although the associations were not statistically significant. One quarter of pedigrees showed a family history of CTEV, and autosomal dominant inheritance was suggested in some of these. Conclusion Uterine restriction did not appear to have a strong influence on ICTEV development in our study. Large population-based studies are needed to clarify the aetiology of this common developmental disorder.